Can Routine Assessment Of Patient Index Data (RAPID)3 Be Used As a Patient Reported Assessment Tool For Patients With Ankylosing Spondylitis? - Cinar, Muhammet; Yilmaz, Sedat; Cinar, Fatma Ilknur; Koca, Suleyman Serdar; Erdem, Hakan; Pay, Salih; Simsek, Ismail (Wiley-Blackwell, 2013)
[Abstract Not Available]
77th Annual Meeting of the American-College-of-Rheumatology / 48th Annual Meeting of the Association-of-Rheumatology-Health-Professionals -- OCT 25-30, 2013 -- San Diego, CA